Wubi Shanyao pills ameliorate diet-induced postmenopausal osteoporosis in mice by enhancing calcium absorption - Su, Xiaorui; Jin, Xiaohu; Yu, Jingjing; Yan, Meiqiu; Su, Jie; Lv, Guiyuan; Chen, Suhong (Frontiers in Pharmacology, 2025)
ObjectiveWubi Shanyao Pills (WSP) is a traditional Chinese botanical formulation known for its gastrointestinal and renal benefits, yet its pharmacological effects on postmenopausal osteoporosis (PMOP) are not well elucidated. This study aimed to evaluate the therapeutic potential of WSP in a diet-induced PMOP model and to investigate its underlying mechanisms related to calcium absorption.MethodsA PMOP-like model was established in perimenopausal mice using a low-calcium, high-phosphorus diet. The mice were treated daily with WSP (0.375, 0.75, or 1.5 g/kg) or alendronate (ALN) (0.14 g/kg). After 17 weeks of treatment, bone microstructure was assessed via small animal CT, along with evaluation of systemic physiological parameters and hematological profiles. Histopathological examinations of the ileum, kidney, and femur were conducted using hematoxylin-eosin (H&E) staining, Alcian blue-periodic acid-Schiff (AB-PAS), and Masson staining. Serum calcium and phosphorus levels were measured by enzyme-linked immunosorbent assay (ELISA). The expression levels of calcium absorption-related proteins were analyzed using immunohistochemistry (IHC), immunofluorescence (IF), Western blotting, and quantitative real-time polymerase chain reaction (qRT-PCR).ResultsWSP exhibited notable pharmacological effects by improving bone mass/quality and serum calcium/phosphorus levels in diet-induced PMOP mice, mediated via upregulating key calcium transport proteins: transient receptor potential vanilloid 5 (TRPV5) and calcium-binding protein (CABP) in the kidney, transient receptor potential vanilloid 6 (TRPV6) and CABP in the ileum, and vitamin D receptor (VDR) in the femur; moreover, WSP reversed PMOP-associated anemia and facilitated tissue structural repair in the kidney, ileum, and femur.ConclusionWSP modulates diet-induced PMOP pathology by promoting calcium absorption via the restoration of organ integrity and regulation of the TRPV5/TRPV6–CABP and VDR-mediated calcium metabolism pathways, thereby underlying its pharmacological effects.